Reading the Bible for all the wrong reasons - Pregeant, Russell (Minneapolis, MN : Fortress Press, 2011)
Russell Pregeant shows that reading the Bible "without interpretation" is impossible. The right question is which assumptions are appropriate. --from publisher description
Introduction: paying attention to the way we read -- More than a fortune cookie: the testimonies of two communities -- Neither fact book nor catechism: re-thinking biblical authority -- Neither science nor anti-science: Genesis, geology, the Big Bang, and Darwin -- Neither crystal ball nor horror show: understanding biblical prophecy -- Neither rigid rules nor billy-stick: the nature of biblical ethics -- The Bible and our beliefs: reflections on Christian doctrine -- Life in the Spirit: the Gospel of grace and demand -- Epilogue: the biblical witness and the Word of God.
Includes bibliographical references.
Keywords: Bible -- Hermeneutics